ChemInform Abstract: Bioactive Clusters Promoting cell Penetration and Nucleic Acid Complexation for Drug and Gene Delivery Applications: From Designed to Self‐Assembled and Responsive Systems. Issue 19 (21st April 2016) - Bartolami, Eline; Bouillon, Camille; Dumy, Pascal; Ulrich, Sebastien
Abstract: Review: [142 refs.